A model of tourism development within the economy (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Currently, attention is increasingly being paid to the non-production sector of the economy, especially tourism, throughout the world, as well as in Uzbekistan. People are trying to spend their free time productively, relax, restore their health, learn about the world, customs and values ​​of peoples. Such services are provided by the tourism sector. In this article, scientific information about the importance of the model of tourism development in the structure of the economy is widely covered.